Innate and adaptive immune responses against coronavirus - Hosseini, Arezoo (2020)
Coronaviruses (CoVs) are a member of the Coronaviridae family with positive‐sense single- stranded RNA. In recent years, the CoVs have become a global problem to public health. The immune responses (innate and adaptive immunity) are essential for elimination and clearance of CoVs infections, however, uncontrolled immune responses can result in aggravating acute lung injury and significant immunopathology. Gaining profound understanding about the interaction between CoVs and the innate and adaptive immune systems could be a critical step in the field of treatment. In this review, we present an update on the host innate and adaptive immune responses against SARS-CoV, MERS-CoV and newly appeared SARS-CoV-2.